2016
DOI: 10.1007/s10616-016-9965-2
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effect of enterolactone in cultured muscle cells and in type 2 diabetic model db/db mice

Abstract: Enterolactone (ENL) is formed by the conversion of dietary precursors like strawberry lignans via the gut microbiota. Urinary concentrations of lignan metabolites are reported to be significantly associated with a lower risk of Type 2 diabetes (T2D). In the present study, antidiabetic effect of ENL and its modes of action were studied in vitro and in vivo employing a rat skeletal muscle-derived cell line, L6 myocytes in culture, and T2D model db/db mice. ENL dose-dependently increased glucose uptake in L6 myot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The glucose uptake stimulatory effect of FSE was determined in L6 cells by a previously reported method [ 60 ] with slight modifications [ 61 , 62 ]. Briefly, L6 cells were grown in 96-well culture plates at 37 °C under 5% CO 2 and cultured for 3–4 days until the cells were confluent.…”
Section: Methodsmentioning
confidence: 99%
“…The glucose uptake stimulatory effect of FSE was determined in L6 cells by a previously reported method [ 60 ] with slight modifications [ 61 , 62 ]. Briefly, L6 cells were grown in 96-well culture plates at 37 °C under 5% CO 2 and cultured for 3–4 days until the cells were confluent.…”
Section: Methodsmentioning
confidence: 99%
“…In the meantime, we have been engaged in studies on antidiabetic effects of food components in type 2 diabetes (T2D) model animals such as KK-A y /Ta [ 9 , 10 ], db/db [ 10 15 ] and ob/ob mice [ 16 , 17 ]. Accumulating clinical evidence suggests that hyperuricemia is strongly associated with abnormal glucose metabolism and insulin resistance (IR) [ 18 ], and diabetic nephropathy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, certain food compounds and dietary strategies are suitable to activate AMPK and to mediate antidiabetic effects. Some intestinal bacteria are able to digest polyphenols and isoflavones from plants and convert it to enterolactone (ENL) or to equol, which both activates AMPK ( 63 , 90 ). Furthermore, ENL ameliorates abnormal lipid metabolism, inhibits anabolic glycogen storage, and improves insulin sensitivity ( 63 , 90 ).…”
Section: Scfa Influence Fat Metabolism Via Activatmentioning
confidence: 99%
“…Some intestinal bacteria are able to digest polyphenols and isoflavones from plants and convert it to enterolactone (ENL) or to equol, which both activates AMPK ( 63 , 90 ). Furthermore, ENL ameliorates abnormal lipid metabolism, inhibits anabolic glycogen storage, and improves insulin sensitivity ( 63 , 90 ). In the respective study it was shown that ENL dose dependently promoted glucose uptake under insulin absent condition, which was completely eliminated by an AMPK inhibitor suggesting that ENL is an antidiabetic substance.…”
Section: Scfa Influence Fat Metabolism Via Activatmentioning
confidence: 99%